Is The Human Development Index Effects The Poverty Rate in Indonesia 2020? - Agus Riyanto (Khazanah: Jurnal Mahasiswa, 2021)
Poverty is a serious problem faced by the Indonesian people from ancient times to thepresent. One that affects the level of poverty in Indonesia is the Human Development Index(IPM). Therefore, it is necessary to research the influence of HDI on the poverty level of eachprovince in Indonesia. The purpose of this study is to analyze the effect of the HumanDevelopment Index on poverty levels in Indonesia. This study uses a quantitative approach with a descriptive analysis method. In additionto descriptive analysis, this study uses a simple linear regression analysis method to determinethe effect of the human development index on the poverty rate in Indonesia. The preliminaryfindings of this study conclude that the human development index affects the poverty level of -0.899. This means that the higher the Human Development Index, the lower the poverty level.From R square shows that 42.8 percent of the Human Development Index variable explains thepoverty variable, while the rest can be explained by other factors. This finding is expected toprovide recommendations to the government regarding human development. Keywords: Human development index, poverty rate, regression